Is Shared Decision-making Associated with Better Patient-reported Outcomes? A Longitudinal Study of Patients Undergoing Total Joint Arthroplasty. Issue 1 (January 2022) - Chrenka, Ella A.; Solberg, Leif I.; Asche, Stephen E.; Dehmer, Steven P.; Ziegenfuss, Jeanette Y.; Whitebird, Robin R.; Norton, Christine K.; Reams, Megan; Johnson, Paul G.; Elwyn, Glyn
Abstract: Background: Although shared decision-making (SDM) has knowledge and satisfaction benefits for patients and is promising, we lack data demonstrating that SDM is associated with better patient-reported functional outcomes. Such data would support the integration and prioritization of SDM into all aspects of orthopaedic care. Questions/purposes: (1) Is a measure of SDM before total joint arthroplasty associated with better patient-reported outcome measures (PROMs) 1 year postoperatively? (2) What is the relationship between the measure of SDM and two measures of patient experience (patient rating of the provider and patient likelihood of recommending the provider) at 1 year postoperatively? Methods: In this observational longitudinal survey-based study, patients receiving an initial THA or TKA from a large, multispecialty medical group in the Midwestern United States were surveyed after they were scheduled for surgery and again at 12 months after their procedure. The three-item collaboRATE measure of SDM was added to existing patient surveys of PROMs. However, the surgeons and their department had no organized approach to SDM during this time. The surveys also included the Oxford knee or hip score and two validated measures of patient experience (patient rating of the provider and whether a patient would recommend the provider). Of the 2779 eligible primary joint arthroplasties that occurred from April 23, 2018 to May 1, 2019, 48% (1334 procedures; 859 TKAs and 485 THAs) of the patients responded to both the preoperative and 12-month postoperative surveys. Most of the patients who were included in the analytic sample were white (93%; 1255 of 1344), with only 3% (37) using Medicaid benefits at the time of surgery. Differences between responders and nonresponders were present and explored in an analysis. Patient responses were analyzed in regression models to estimate the association between preoperative collaboRATE scores and the Oxford knee or hip scores, and patient experience measures 12 months postoperatively. Results: There was a moderate, positive association between preoperative collaboRATE scores and the Oxford scores at 12 months, after adjustment for potential confounders such as patient age and preoperative functional score (β = 0.58; 95% CI 0.14-1.02; p = 0.01). Similarly, patients with preoperative collaboRATE scores had marginally higher patient experience scores at 12 months postoperatively (β = 0.14; 95% CI 0.05-0.24; p = 0.003) and were more likely to recommend their surgeon (OR 1.43; 95% CI 1.11-1.84; p = 0.005). The patient experience measures were also modestly correlated with collaboRATE scores in cross-sectional associations, both preoperatively and at 12 months postoperatively (0.29 ⩽ r ⩽ 0.54; p < 0.01). Conclusion: The association between preoperative collaboRATE scores and Oxford hip or knee scores suggests that SDM could be one tool to encourage better outcomes. Although previous studies have shown that SDM can improve patient experience, the lack of a strong correlation in our study suggests that PROMs and experience measures are separate domains, at least partly. Improving preoperative SDM between the surgeon and patient might help improve surgical outcomes for patients undergoing TKA and THA. Level of Evidence: Level II, therapeutic study.